THE HIERARCHICAL APPROACH TO SOCIAL-GEOGRAPHIC DEFINITION OF THE CATEGORY «MEDICAL AND DEMOGRAPHIC SITUATION» - Молікевич, Роман (Human Geography Journal, 2015)
In this article the author's interpretation of the category «medical-demographic situation» using a hierarchical approach is justified. The author puts the focus on relatively «youth» and the lack of theoretical grounding of category. Proved fundamental difference in the use of this category in social geographical research  and in other sciences. A number of multi-level categories are analyzed and their contribution to the formation of categories’ «medical and demographic situation» content is described. The author characterized the grounds and innovativeness of use the approach in socio-geographical studies.